PERBANDINGAN HASIL BELAJAR MODEL PEMBELAJARAN NHT DAN GI DENGAN MEMPERHATIKAN MOTIVASI BERPRESTASI - Vivien Barcellena Fentisari; Eddy Purnomo; Yon Rizal (FKIP Unila, 2014)
This research aims to know difference of learning outcomes between students of grade VIII SMPN 3 Natar who are learned using NHT model with GI model. This research was clasified as an experimental research with comparative approach. Population in this research is 188 students and samples 76 students (2classes) were taken by using cluster random sampling. The results of research showed: (1) There is difference in learning outcomes between students who are learning using NHT model with GI model. (2) The average in learning outcomes is taught using a model of learning NHT model is higher than that taught using the GI model for students who have low achievement motivation. (3) The average in learning outcomes is taught using a model of learning NHT model is lower than that taught using the GI model for studenst who have high achievement motivation. (4) There is interaction between model of learning and achievement motivation of students in learning outcomes.Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar ekonomi antara siswa kelas VIII SMPN 3 Natar yang diajarkan menggunakan model NHT dan GI. Populasi dalam penelitian ini adalah 188 siswa dan sampel 76 siswa (2kelas) diambil dengan menggunakan cluster random sampling. Hasil penelitian menunjukkan: (1) Ada perbedaan hasil belajar antara siswa yang pembelajarannya menggunakan model NHT dengan model GI. (2) Rata-rata hasil belajar yang diajar menggunakan model pembelajaran NHT lebih tinggi dibandingkan yang diajar dengan model pembelajaran GI bagi siswa yang memiliki motivasi berprestasi rendah. (3) Rata-rata hasil belajar yang diajar menggunakan model pembelajaran NHT lebih rendah dibandingkan yang diajar dengan model pembelajaran GI bagi siswa yang memiliki motivasi berprestasi tinggi. (4) Ada interaksi antara model pembelajaran dengan motivasi berprestasi siswa terhadap hasil belajar.Kata kunci: gi, hasil belajar, motivasi berprestasi, nht